2022
DOI: 10.1021/acs.jpclett.1c04020
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Induced Phase Transition of Nanowires on Germanium(001) Surfaces

Abstract: The manipulation of conductive nanowires (NWs) on semiconductor platforms provides important insights into the fabrication of nanoscale electronic devices. In this work, we directly observed the electric field-induced phase transitions in atomic Au-NWs self-assembled on Ge(001) surfaces using scanning tunneling microscopy (STM). The tunneling electrons and electric fields underneath a STM tip apex can effectively trigger a phase transition in Au-NWs on Ge(001) surfaces. Such phase transitions are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Noble metals (i.e., Au and Pt) are known to trigger the selfassembly of atomic NWs on Ge(001) surfaces. 13,[26][27][28][29] DFT calculations revealed that self-organized NWs on Pt/Ge(001) surfaces are constituted by under-coordinated Ge atoms (Fig. 1b, S1a and b †), suggesting the presence of dangling bonds on the NWs.…”
Section: Resultsmentioning
confidence: 99%
“…Noble metals (i.e., Au and Pt) are known to trigger the selfassembly of atomic NWs on Ge(001) surfaces. 13,[26][27][28][29] DFT calculations revealed that self-organized NWs on Pt/Ge(001) surfaces are constituted by under-coordinated Ge atoms (Fig. 1b, S1a and b †), suggesting the presence of dangling bonds on the NWs.…”
Section: Resultsmentioning
confidence: 99%